Au SINE element from the cultivated yerba mate tree (Ilex paraguariensis) - Aguilera, Patricia Mabel (2021)
SINE2_Ipa. Au SINE element from the cultivated yerba mate tree (Ilex paraguariensis). 1..81 feature=tRNA-related region; 14..24 feature=A box; 57..67 feature=B box; 82..163 feature=tRNA-unrelated region; 164..170 feature=tail. >1 thousand copies in the genome of yerba mate (GCA_905181385.1). It is similar to SINE2-1_JC, SINE2-2_STu, SINE2-1_TAe, SINE-5_Mad and SINE2-1_PD.